1993
DOI: 10.1080/03079459308418925
|View full text |Cite
|
Sign up to set email alerts
|

Separation of phagocytic leukocytes from the peripheral blood of chickens

Abstract: SUMMARYPhagocytic leukocytes were separated from the peripheral blood of chickens using a one-step Percoll density gradient technique. Heterophils recovered from two fractions of the gradient were of 96.9 to 99.8% purity and were fully viable and functional, as demonstrated by their capacity to phagocytose latex beads and staphylococci. Adherent mononuclear cells were cultured from specific gradient fractions and shown to phagocytose staphylococci.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
3
1
0
Order By: Relevance
“…To the best of our knowledge, the distribution of cells in the buffy coat of selected reptile and nonpoultry avian species has never been studied in detail. Still, our data are in accordance with a classical report‐based separation of cells by Percoll gradients . This study by Mills and Wilcox with chicken blood reported that thrombocytes appear admixed with lymphocytes in lighter fractions (which corresponds to the upper buffy coat parts), whereas denser fractions contained mostly heterophils.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…To the best of our knowledge, the distribution of cells in the buffy coat of selected reptile and nonpoultry avian species has never been studied in detail. Still, our data are in accordance with a classical report‐based separation of cells by Percoll gradients . This study by Mills and Wilcox with chicken blood reported that thrombocytes appear admixed with lymphocytes in lighter fractions (which corresponds to the upper buffy coat parts), whereas denser fractions contained mostly heterophils.…”
Section: Discussionsupporting
confidence: 93%
“…Still, our data are in accordance with a classical report‐based separation of cells by Percoll gradients . This study by Mills and Wilcox with chicken blood reported that thrombocytes appear admixed with lymphocytes in lighter fractions (which corresponds to the upper buffy coat parts), whereas denser fractions contained mostly heterophils. These cells were also present among nucleated erythrocytes, and to a lesser extent in lighter fractions of lymphocytes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Blood was obtained from the brachial vein in an heparinized syringe, afterwards it was diluted using an equal volume of Hank's balanced saline solution (HBSS) and homogenized. Blood was carefully deposited in a gradient with 70 and 80% of Percoll (Pharmacia) and centrifuged to 1150 g for 30 min at room temperature as has been previously reported (Mills & Wilcox, 1993;Desmidt et al ., 1996). Cells were washed twice with HBSS by centrifugation (1150 g for 10 min) and the pellet was suspended in RPMI medium containing 10% fetal bovine serum and 10 UI/ml penicillin, and 10 mg/ml streptomycin (complete RPMI medium).…”
Section: Proliferation Assaysmentioning
confidence: 99%